Single-cell antigen receptor sequencing in pigs with influenza - Weihong Gu; Darling Melany de Carvahlo Madrid; Yuhan Wen; Sadie Clements; Laurie Touchard; Nathan Bivens; Grant Zane; Mingyi Zhou; Kiho Lee; John P. Driver (Communications Biology)
Abstract Single-cell RNA sequencing (scRNAseq) has accelerated characterizing cellular phenotypes in pigs under healthy and diseased conditions. To pair scRNAseq with immune receptor profiling, we developed porcine-specific T cell receptor (TCR) and B cell receptor (BCR) enrichment primers that are compatible with the 10 × Genomics VDJ sequencing protocol. Using these assays, we profiled the immune repertoire of cryopreserved lung cells from CD1D-expressing and CD1D-deficient pigs after one or two infections with influenza A virus (IAV) to examine whether natural killer T (NKT) cells influence pulmonary TCR and BCR receptor repertoires. We also profiled T cells longitudinally sampled from the lung fluid of IAV-vaccinated and -infected pigs to track clonal expansion. While all pigs presented highly diverse repertoires, pigs re-exposed to IAV had more expanded T cell clonotypes with activated phenotypes, suggesting potential IAV-reactive clones. Our results demonstrate the utility of high throughput single cell TCR and BCR sequencing in pigs.